THE INFLUENCE OF COMPETENCE, MOTIVATION AND ORGANIZATIONAL COMMITMENT TO THE PERFORMANCE OF FINANCIAL MANAGEMENT OF WORK UNIT GOVERNMENT DEVELOPMENT IN MINAHASA REGENCY - Kaunang, Yudith Pius Stevan (Universitas Sam Ratulangi, 2020)
Government Regulation (or Peraturan Pemerintah-PP) Number 58 of year 2005 concerns Regional Financial Management and Regulation of the Minister of Home Affairs (or Permendagri) Number 13 of 2006 concerning Regional Financial Management Guidelines as amended several times, most recently by Permendagri Number 21 of 2011 it is stated that regional finance is managed in an orderly manner, obeying the laws and regulations, efficiently, economically, effectively, transparently, and responsibly by paying attention to the principles of justice, propriety, and benefits to society.Financial management in the regions requires a reliable application, which is an application that can process data (input) and produce information (output) to assist management in making decisions, and can produce financial reports and other financial information more comprehensively, includes information about the regional financial position, financial performance conditions, and accountability of local governments.In term to optimize the performance of regional financial management,the Financial and Development Supervisory Agency (or Badan Pengawasan Keuangan dan Pembangunan) has responded positively through the development of a financial SIMDA application program. This SIMDA financial application has been integrated starting from the budgeting function, regional financial administration functions, to the accounting and reporting functions.The type of data used in this study is, Qualitative Data is data obtained from the technique of gathering through a Questionnaire.This data collection was carried out on 48 Regional Work Units in the Minahasa Regency. The results of this study indicate that competency, motivation and organizational commitment have a significantly positive and partially significant impact on performance of financial management.